KEPUASAN KONSUMEN OTOMODIFIED DITINJAU DARI ASPEK KUALITAS PELAYANAN USAHA - Ika Dana Rahayu; Leonard Adrie Manafe; Adi Siswandono; Putri Intan Alfiani (Jurnal Ekonomi Integra, 2022)
This study aims to determine the quality of service in terms of tangible indicators, reliability, responsiveness, assurance and empathy in Otomodified stores that affect consumer satisfaction so that it will lead to recommendations from the consumer to the people around him. The method in this study is a qualitative approach, data collection techniques are carried out by filling out questionnaires to consumers and direct interviews with a number of 30 informants. From the results of the recapitulation of interview data in this study, tangible indicators/physical evidence that most dominate on consumer satisfaction so that consumers recommend the store to friends or also the people around them. Physical evidence related to the selection of a very strategic business location, close to the highway, easy parking access, and neat product arrangement. It has become a must for every business actor to always prepare a mature strategy in his business, one example is the selection of a strategic location and a neat product arrangement that can trigger the birth of a recommendation from buyers.